Het Apollohuis 1980-1990 : Exhibitions, Concerts, Performances, Installations, Lectures, Publications. - Donker, Janny; Panhuysen, Paul; Yocarini, Titus; Het Apollohuis, Eindhoven (Eindhoven : Het Apollohuis, 1990)
This book Het Apollohuis 1985-1990 provides an outline of the programme series at Het Apollohuis from the fall of 1985 until the fall of 1990. Together with the book Het Apollohuis 1980-1985 it completes the report of ten years of activities. Over the last five years 102 exhibitions and installations and 163 concerts and performances have been presented. The programme involved about 400 artists from all over the world. In this publication all these activities are summarized in short descriptions. The wealth of photographs is a memento of all those special moments which could be experienced in this special place and time and again, they convince over their singular context : Het Apollohuis.
Kersten, Willem Jan ; Koenraads, Guus ; Wonders, José ; Tan, Laurens ; Zwerver, Ton ; Ferrer, Esther ; Radigue, Eliane ; Johnson, Tom ; Schulte, Nico ; de Blauw, Arnoud ; Geuer, Juan ; Demnig, Gunter ; Honing, Henkjan ; van Riper, Peter ; Dörstel, Wilfried ; Marclay, Christian ; Szemzö, Tibor ; Forgacs, Peter ; Poth, Uwe ; Hutchison, F.M. ; Maris, J.W. ; Tegge, Ulrich ; Schüler, Mannfred ; Stock, Bodo ; Brambring, Peter ; Henning, Reinhard ; Gajewski, Henryk ; Panhuysen, Paul ; Plotnicka, Anna ; Swidzinski, Jan ; Sips, Roland ; Erben, Josef ; Rheinsberg, Raffael ; Eller, Ulrich ; Suzuki, Nanaé ; Langebartels, Rolf ; Schon, Eva Maria ; Radermacher, Norbert ; Ro, Eun Nim ; Hoekstra, Joost ; Diekmann, Günter ; Nieslony, Boris ; Mahn, Inge ; Weinstein, David ; Viner, Darrell J. ; de Laar, Jeroen van ; van den Berg, Jan ; Bien, Ania ; Wagner, Sokhi ; Neumann, Ginger ; Potthoff, Kerstin ; Ox, Jack ; Tappeser, Rainer ; Villers, Bernard ; Weinfeld, Jean ; Riches, Martin ; Kosugi, Takehisa ; Rickels, Horst ; Pomeroy, Jim ; Fähndrich, Walter ; Bazelmans, Fé ; Gees, Paul ; Haimsohn, Jana ; Gould, Melissa ; Tallman, Susan ; Bastian, Pierre ; Oltshoorn, Bernard ; Devens, Dré ; van Bommel, Frans ; Monshouwer, Rien ; Goedhart, Johan ; Ellens, Kie ; Kramer, Paul Dieter ; Hamersma, Gerlof ; Parlevliet, Nico ; Samens, Ralf ; Maier, Pepi ; Schatzl, Leo ; Bitter, Sabine ; Weber, Helmut ; Lerman, Richard ; Kardos, Sándor ; Hunt, Jerry ; Angelmaier, C. ; Berke, Sybille ; Frisch, Mechtild ; Wassermann, Gudrun ; Andersen, Eric ; Nijman, Erna ; Kubiczak, Harald ; Dutrieux, Daniel ; Hansma, Siebe ; van der Putten, Hendri ; Vloemans, Piet ; Boersma, Pieter ; Niblock, Phill ; Arcand, Pierre-André ; Muyle, Johan ; Fox, Terry ; van der Beek, Jeroen ; DeMarinis, Paul ; etc.
Publications Het Apollohuis 1980-1990 p. 138
Engels
boek